Redução de cromo hexavalente em filtro biológico de fluxo contínuo - Dalcin, Maurielem Guterres (2009)
Hexavalent chromium (Cr (VI)) is a heavy metal, highly toxic and carcinogenic for alive beings. It is used thoroughly in industries of different such segments as: steel industries, metal works, textile industries, tanning, nuclear power stations, of galvanoplasty and paints. Due to the wide application, the hexavalent chromium is found in high concentrations in the industrial effluents and it presents a serious risk to the health of animals and plants. This work had economically for purpose to propose an alternative viable for the treatment of polluted effluent for hexavalent chromium, since the most employed treatments (physical and chemical) they present high costs and they generate by-products in high amount. The objective was to accomplish the reduction of the hexavalent chromium for trivalent chromium form using microorganisms capable to reduce this composed. The employed microorganisms in the present study were a mixed culture (C1), that it was initially adapted to the half containing yeast residual brewer as main source of carbon (M1), in initial concentrations of 31,25; 58,82; 83,33 and 105,26 mg/L of hexavalent chromium. The concentration of 58,82 mg/L presented the largest values of removal of chrome, in a range of 56 to 73%. Distributions of times of residence (DTRs) were accomplished to evaluate the behavior of the regime of the biological filter and to esteem the real behavior of the drainage in the bioreactor. The medium time of residence used in most of the experiments was of 24 h (recommended by the legislation). The influence of the pH in the state of oxidation of the chrome was studied and it was verified that for smaller pH values than 4 happened the chemical reduction of the hexavalent chromium. Four preliminary assays were used to beginning to the operation of the bioreactor: the first had the objective to evaluate the transient regime, but for operational difficulties it cannot be evaluated. For the second test, small taxes of removal of chrome were observed due to the low time of residence used (8 h) - minimum recommended for biological filters. In the third tests, it was observed an intermediate removal that was increased in the fourth experiment by the change of the culture medium. Starting from these results it was possible to establish the ranges of the chosen variables: pH (5,5 to 8) and CCr0, (concentration of initial hexavalent chromium - 15 to 165 mg/L) and to accomplish a DCC (Center Composite Design) the response was the removal of hexavalent chromium. The boundary curves and surface response showed the tendency of optimization of the hexavalent chromium removal that is in values of CCr0 (3,94 mg/L) and of pH (6,2). For describe the process hexavalent chromium removal mathematically, the kinetic model of Michaelis-Menten was used. This model describes in an appropriate way the variation of chromium concentration along of the bioreactor.